Food security and maritime security: A new challenge for the European Union's ocean policy. (October 2019) - Suárez-de Vivero, Juan L.; Rodríguez Mateos, Juan C.; Florido del Corral, David; Barragán, María José; Calado, Helena; Kjellevold, Marian; Miasik, Ewelina Janowska
Abstract: This paper revolves around the role that food-from-the-sea plays in European maritime security. It aims to illustrate the links between food, fisheries, and maritime security by considering these as coexisting attributes of security in general and of maritime (in)security, in particular. The article analyzes three dimensions of this issue: the links between food security, maritime security and maritime policy; the principles that inspire the Common Fisheries Policy and their implications for the food system; and the complexity involved in the trade relations between European markets (EU) and non European suppliers (the case of Cape Verde). The relevant conclusions that can be established are i) the EU's food security policy shows little sign of changing the course of its fisheries policy objectives; ii) The different dimensions of the relationship between fisheries and food security should not be neglected. In fact, from a local perspective, the concept of food sovereignty could be applied to some of the European Union's coastal territories. Therefore, European decision-makers should not ignore the fact that subsistence fisheries are still a strategy in some European coastal areas, where access to maritime resources is the key to their economies. Highlights: Food insecurity is not limited to the developing world. EU ocean policy tackles food security challenges. Ideological basis of food notion are seldom taken into consideration in EU policies. Small scale fisheries are still a strategy in some European coastal areas. EU documents on maritime and fisheries policies do not mention food sovereignty.